The Silmarillion - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Houghton Mifflin, 1977)
Includes "The Silmarillion," and four short works: "The Ainulindale," "The Valaquenta," "The Akallabeth," and "Of the Rings of Power.".